(untitled) (Research, Society and Development, 2021)
The article aims to investigate the perceptions of preoperative patients after surgery cancellation in a surgical clinic unit of a public hospital in Belo Horizonte, Minas Gerais. This is a qualitative study carried out with five patients from the surgical clinic, aged 18 years or over, 12 hours after the cancellation of the surgery. The content of the interviews with patients aged 41 to 68 years, two single and three married, four male and one female were transcribed and submitted to Bardin’s content analysis. The hospitalization diagnoses were: leg necrosis, arterial thrombosis, foot amputation, hemorrhagic stroke, herniated disc in the lumbar region. The categories analyzed were: patient arrival at the hospital, communication of surgery cancellation and feelings regarding surgery cancellation. Patients first sought the emergency care unit when they could no longer bear the pain, being referred to the hospital to undergo the surgical procedure. The cancellation of the surgery was notified by the doctor, nurse or physiotherapist and the patient thought that his case was not serious, he felt resigned, other situations generated anger, revolt, anxiety, expectation, sadness, rejection, longing, joy, tranquility. This study made it possible to know some psychological aspects associated with the preoperative patient, showing that there is a need to improve management strategies to design an effective line of care, capable of providing users of health services with security regarding the care they received offered.